Spatial and social mobility in England: The persistence of the ‘Escalator’ effect for the millennial generation - Yu, Yang (Population space and place, 2023)
Regional disparities in social mobility have long been apparent in Britain. Recent decades have seen a growing level of spatial inequalities in terms of social, economic and employment opportunities. Empirical studies suggest not only what do your parents do, but also where do you come from, profoundly influences one's life opportunities, London and the Southeast are consistently shown to be areas with more social mobility than the rest of country. This study presents an updated estimate of the extent of social mobility across regions in England, and more importantly, how this has been conditional on cross‐region migration. By using national representative survey data covering a decade (2005–2015), the results show considerable variations in the regional estimates of both absolute and relative mobility. In particular, London was found to be leading on social mobility measures in nationwide comparisons, supporting previous findings that London plays an important national role in Britain's social mobility. In addition, separate analysis for samples of cross‐region ‘movers’ and ‘stayers’ suggests that migration is associated with social upward mobility, with London still functioning as an ‘escalator‘ region providing better opportunities for those who move there from elsewhere the country. This persistence of the ‘escalator region’ effect for the millennial generation in England underlines how unequal economic geography continues to shape opportunity and trajectories of mobility for individuals.